The morbidity and mortality rates following surgery in metastatic spine disease patients - Sami Aleissa; Faisal Konbaz; Firas Alsebayel; Abdullah Eissa; Nawaf Alogayyel; Ali Alhandi; Muath Almajed; Anouar Bourghli; Fahad Alhelal; Majed Abaalkhail (Journal of Spine Practice)
Background: Metastasis is one of the most frequent causes of cancer-related deaths globally. Several studies have investigated the surgical outcome of a metastatic spine; however, the results are discordant. This research aims to study the mortality and morbidity rates of surgical intervention for metastatic spine disease and the predictors of postoperative complications in a tertiary care center.